2004
DOI: 10.1104/pp.103.031930
|View full text |Cite
|
Sign up to set email alerts
|

The CPH1 Gene of Chlamydomonas reinhardtii Encodes Two Forms of Cryptochrome Whose Levels Are Controlled by Light-Induced Proteolysis  

Abstract: Cryptochromes are proteins related to DNA photolyases and have been shown to function as blue-light photoreceptors and to play important roles in circadian rhythms in both plants and animals. The CPH1 gene from Chlamydomonas reinhardtii was originally predicted to encode a putative cryptochrome protein of 867 amino acids with a predicted molecular mass of 91 kD (Small et al., 1995). However, western blotting with antibodies specific to the CPH1 protein revealed the presence of two proteins that migrate at appa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
60
0

Year Published

2005
2005
2020
2020

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 70 publications
(67 citation statements)
references
References 40 publications
5
60
0
Order By: Relevance
“…The accumulation of aCRY exhibits an amplitude change of about twofold within a light/dark cycle (Figures 2A and 2B). In contrast to CPH1 (Reisdorph and Small, 2004), aCRY is not rapidly degraded in the light. The highest levels of this protein are observed at the beginning of and extending to the middle of the day (LD2 and LD6), with its lowest values at the beginning of the night (LD14) (Figures 2A and 2B).…”
Section: Resultsmentioning
confidence: 95%
See 1 more Smart Citation
“…The accumulation of aCRY exhibits an amplitude change of about twofold within a light/dark cycle (Figures 2A and 2B). In contrast to CPH1 (Reisdorph and Small, 2004), aCRY is not rapidly degraded in the light. The highest levels of this protein are observed at the beginning of and extending to the middle of the day (LD2 and LD6), with its lowest values at the beginning of the night (LD14) (Figures 2A and 2B).…”
Section: Resultsmentioning
confidence: 95%
“…The responses of this photoreceptor to blue light have been thoroughly investigated in vitro (Immeln et al, 2007(Immeln et al, , 2010Langenbacher et al, 2009). However, in vivo studies have been limited, although it was shown that the expression pattern of C. reinhardtii CPH1 tracks the diurnal light/dark cycle, with lightdependent CPH1 degradation mediated by the proteasome pathway; this degradation involves blue light, but surprisingly, red light also participates in the degradation process (Reisdorph and Small, 2004).…”
Section: Introductionmentioning
confidence: 99%
“…Although it is an attractive candidate of photoreceptor for light-induced ROC15 degradation, we could not exclude the possibility of the existence of other unknown red-light photoreceptors in C. reinhardtii. Another cryptochrome homolog, Chlamydomonas photolyase homolog 1 (CPH1), shows a rapid decrease in protein accumulation level, similar to ROC15, after exposure to blue or red light because of proteasomedependent protein degradation (39). The light-induced degradation of ROC15 and CPH1 may occur through the same pathway.…”
Section: Discussionmentioning
confidence: 99%
“…Specifically, Chlamydomonas possesses a single phototropin (Huang and Beck, 2003), rhodopsins, including channelrhodopsins (Nagel et al, 2002(Nagel et al, , 2003Kateriya et al, 2004), a plant-like cryptochrome (Reisdorph and Small, 2004), and an animal-like cryptochrome that responds to both blue and red light (Beel et al, 2012). Furthermore, a histidine kinase rhodopsin was recently characterized that exists in both UV-A-and blue-light-absorbing isoforms (Luck et al, 2012).…”
Section: Introductionmentioning
confidence: 99%